Advances in Uveal Melanoma: From Molecular Pathogenesis to Precision Diagnostics and Personalized Therapies: Narrative Overview - Shatnawi, Raed; Al-Hyari, Ahmad; Al-Latayfeh, Motasem; Abu Ain, Mohammad; Shatnawi, Husam; Shatnawi, Yazan; A. Yousef, Yacoub (Asian Pacific Journal of Cancer Biology, 2025)
Objective: This review aims to summarize recent progress in the molecular understanding, diagnostic strategies, and treatment innovations in uveal melanoma (UM), the most common primary intraocular malignancy in adults. Emphasis is placed on the integration of precision diagnostics and emerging therapies that may improve clinical outcomes in high-risk cases. Materials and Methods: A narrative literature review was conducted using databases including PubMed, Scopus, Web of Science, and Google Scholar, covering the years 2020 to 2024. Keywords used included “uveal melanoma,” “liquid biopsy,” “circulating tumor cells,” “gene mutations,” “immunotherapy,” and “precision oncology.” Relevant peer-reviewed articles, clinical trials, and reviews were selected based on methodological quality and relevance to the scope of the review. Results: Uveal melanoma most frequently arises in the choroid and is genetically distinct from cutaneous melanoma. It is primarily driven by mutations in guanine nucleotide-binding protein G(q) subunit alpha (GNAQ), guanine nucleotide-binding protein G(q) subunit alpha-11 (GNA11), BRCA1 associated protein-1 (BAP1), eukaryotic translation initiation factor 1A X-linked (EIF1AX), and splicing factor 3B subunit 1 (SF3B1). These mutations activate key signaling pathways such as mitogen-activated protein kinase (MAPK) and phosphoinositide 3-kinase/protein kinase B (PI3K/AKT), influencing prognosis and therapeutic response. Diagnostic advancements include high-resolution imaging and liquid biopsy techniques, which enable detection of circulating tumor cells, circulating tumor DNA, and microRNAs. Standard treatments include radiation therapy (plaque brachytherapy) and surgical interventions. Novel therapeutic approaches such as tebentafusp (a T-cell receptor therapy), oncolytic viruses, chimeric antigen receptor (CAR) T-cell therapy, suicide gene constructs, and RNA interference show promise in clinical and preclinical settings. Conclusion: A precision medicine approach that integrates molecular diagnostics, artificial intelligence-enhanced liquid biopsy, and novel systemic therapies is transforming the management of uveal melanoma. These innovations may enable earlier detection, more accurate risk stratification, and targeted treatment, potentially improving survival and preserving vision in affected patients.